Association between the behavioral response during social exclusion and recalled childhood maltreatment. (January 2023) - Barton, Barbara B.; Reinhard, Matthias A.; Goerigk, Stephan; Wüstenberg, Torsten; Musil, Richard; Ehring, Thomas; Jobst, Andrea; Dewald-Kaufmann, Julia; Padberg, Frank
Abstract: Social exclusion is a critical event for mental health. Patients with interpersonal dysfunction, e.g., with borderline personality disorder (BPD) or persistent depressive disorder (PDD), are particularly vulnerable, often based on their experiences of early adversity in life. The etiological pathways from childhood maltreatment (CM) to current behavior during social exclusion are still underexplored. This cross-diagnostic study investigated the relationship between self-reported CM and behavioral reaction to social exclusion in an experimental paradigm (Cyberball). Data from 140 subjects including patients with BPD and PDD as well as healthy controls were analyzed. The effect of CM (Childhood Trauma Questionnaire, CTQ) on behavior to social exclusion during Cyberball (ball tossing behavior) was analyzed including rejection sensitivity (RS) as a mediator. In the whole sample, the CTQ score ( B  = -.004, p  < .05) as well as the emotional neglect subscore ( B  = -.016, p  < .01) were associated with a reduced ball tossing behavior towards the excluder. There were no significant indirect effects involving RS. These current findings support the relationship between CM and an altered interpersonal response in critical interpersonal situations. Larger cohorts with multidimensional data in social domains are warranted to further investigate the link between CM and current interpersonal dysfunction. Highlights: Association between childhood maltreatment (CM) and reaction to social exclusion and Among CM subtypes, especially association with emotional neglect. First study on this pathway with data from an experimental paradigm (Cyberball). Findings in a cross-diagnostic sample of healthy subjects and vulnerable groups. Rejection sensitivity did not mediate the effect of CM on prosocial behavior.